2017
DOI: 10.1186/s13068-017-0908-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stakeholders’ attitudes towards biodiesel

Abstract: BackgroundConcern about the inevitable depletion of global energy resources is rising and many countries are shifting their focus to renewable energy. Biodiesel is one promising energy source that has garnered much public attention in recent years. Many believe that this alternative source of energy will be able to sustain the need for increased energy security while at the same time being friendly to the environment. Public opinion, as well as proactive measures by key players in industry, may play a decisive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 66 publications
5
17
0
Order By: Relevance
“…The results revealed that perceived benefit emerged as the most significant direct predictor of attitude towards the ORS (β = 0.618, p<0.001) (Fig 2), suggesting that when the respondents in the Klang Valley perceived the ORS as having higher benefits, they would be more positive towards the technique. This finding is supported by previous studies where perceived benefit emerged as the main factor of attitudes to GM mosquito [16], and biodiesel products [37]. However, in this study, the perceived risk did not have any association with attitudes but had a negative association with the perceived benefit of ORS (β = -0.136, p<0.01) (Fig 2).…”
Section: Relationship Among the Constructssupporting
confidence: 89%
See 1 more Smart Citation
“…The results revealed that perceived benefit emerged as the most significant direct predictor of attitude towards the ORS (β = 0.618, p<0.001) (Fig 2), suggesting that when the respondents in the Klang Valley perceived the ORS as having higher benefits, they would be more positive towards the technique. This finding is supported by previous studies where perceived benefit emerged as the main factor of attitudes to GM mosquito [16], and biodiesel products [37]. However, in this study, the perceived risk did not have any association with attitudes but had a negative association with the perceived benefit of ORS (β = -0.136, p<0.01) (Fig 2).…”
Section: Relationship Among the Constructssupporting
confidence: 89%
“…Studies on consumer behaviour have indicated that perceived benefit and risk strongly influenced individual responses regarding acceptance of technology [36][37][38][39][40][41]. Perceived benefit is a positive predictor of attitude, while perceived risk is a negative predictor of attitude.…”
Section: Perceived Benefit and Riskmentioning
confidence: 99%
“…Mustapa et al (2019) have suggested engagement as one of the factors in the conceptual framework for determining behavioral intention to adopt pharmacogenomic techniques in Malaysia. The mean score of the engagement factor in this study has shown a moderate level and has similarity finding the score on biodiesel products (Amin et al, 2017) and xenotransplantation (Amin et al, 2017). In a separate study, Amin et al (2014) found that demographic factors such as gender may also affect the level of awareness, in which a group of females is highly aware of accepting genetically modified food and medicine.…”
Section: Participation: Stakeholder's Engagementsupporting
confidence: 65%
“…Therefore, engagement involves a certain degree of stakeholder's motivation to accept or reject a matter depending on positive or negative attitude in determining their behavioral intention; the more positive behavior, the more positive on their participation (Chiu & Qijie, 2012). Past studies have shown an interplay of association between engagement with their perceived benefits in shaping good attitude toward GM rice (Amin & Hashim, 2015b), biodiesel products (Amin et al, 2017), and xenotransplantation (Amin et al, 2017). Mustapa et al (2019) have suggested engagement as one of the factors in the conceptual framework for determining behavioral intention to adopt pharmacogenomic techniques in Malaysia.…”
Section: Participation: Stakeholder's Engagementmentioning
confidence: 99%
“…Biodiesel is also known for minimizing environmental pollution due to the reduction in exhaust emission and toxic elements (Chen et al, 2018). However, perceived benefits of biodiesel production and use need to be critically analyzed prior to its economic feasibility and commercialization (Amin et al, 2017;Hanif et al, 2018).…”
Section: Introductionmentioning
confidence: 99%